Survival status and predictors of mortality from severe community-acquired pneumonia among under-five children admitted at Debre Tabor comprehensive specialized hospital: a prospective cohort study - Kassaw, Amare; Kerebih, Gashaw; Zeleke, Shegaw; Chanie, Ermias Sisay; Dessalegn, Nigatu; Bante, Berihun; Teshome, Asefa Ageghehu; Chekole, Bogale; Gelaw, Belete; Bayih, Wubet Alebachew; Tesfaw, Aragaw; Feleke, Dejen Getaneh; et al. (Frontiers in Pediatrics, 2023)
Background Globally, Pneumonia continues to be the leading cause of mortality among under-five children. Ethiopia ranks fourth out of 15 countries worldwide in terms of the highest death rate of under-five children due to severe community-acquired pneumonia (SCAP). However, to date, there is no recent study that shows survival status and predictors of mortality from SCAP. Therefore, this study aimed to determine survival status and predictors of mortality from this dangerous disease among under-five children. Methods A facility-based prospective cohort study was conducted from 1 November 2021 to 31 October 2022 at Debre Tabor comprehensive specialized hospital. All under-five children with SCAP admitted during the study period were included. Participants were selected using a systematic sampling technique. The collected data were coded, edited, and entered into epi-data version 4.2 and then exported to STATA version 17 for further analysis. The Kaplan Meier failure estimate with log-rank test was employed to determine the survival estimates. A cox-proportional hazard regression model was fitted to identify significant variables. Results The overall incidence density rate of mortality was 5.7 /1000 children with a median hospital stay of 8.2 days. Heart disease (AHR: 4.37; 95%CI: 1.68–11.32), previous admission of SCAP (AHR: 3.87; 95% CI: 1.31–11.43), WFL < −3Z score (AHR: 3.57; 95% CI: 1.02–12.42), impaired consciousness level at admission 3.41(1.14–10.19), and pleural effusion (AHR: 3.42; 95%CI: 1.18–9.93) were significant predictors of mortality. Conclusion In this study, the survival probability of children with SCAP was low. Children with heart disease, previous admission of SCAP, WFL < −3Z score, impaired consciousness level at admission, and pleural effusion had low survival. Therefore, much emphasis is needed on children with SCAP, particularly those with identified predictors.